1999
DOI: 10.1046/j.1529-8817.1999.3510128.x
|View full text |Cite
|
Sign up to set email alerts
|

THE atpA GENE CLUSTER OF GUILLARDIA THETA (CRYPTOPHYTA): A PIECE IN THE PUZZLE OF CHLOROPLAST GENOME EVOLUTION

Abstract: We cloned and sequenced the genes of the atpA (atp1) cluster, together with its upstream and downstream sequences, of the chloroplast genome of the cryptomonad Guillardia theta Hill et Wetherbee and used gene signatures, predicted amino acid sequences, and gene arrangements for phylogenetic inferences. The Guillardia atpA cluster contains the genes atpI,H,G,F,D,A in the given order, thus reflecting the cyanobacterial/red algal/chromophyte gene arrangement. In addition, the order of both the upstream sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In chlorarachniophytes and cryptomonads, which contain periplastid ERs (Corliss 1994) but do not belong to the stramenopiles in rRNA trees (Cavalier-Smith 1993; Van de Peer and De Wachter 1997), the periplastid space harbors remnants of an engulfed cell's nucleus, the nucleomorph (Gilson, Maier, and McFadden 1997), indicating that these algae originated via eukaryote-eukaryote endosymbioses between a phagotrophic host cell and an unicellular microalga (Gibbs 1981;Sitte 1993;McFadden and Gilson 1995;Douglas 1998). Although diatoms, like most photosynthetic heterokontflagellated protists, have not preserved a nucleomorph, molecular data indicate that their four membrane-bounded plastids descend from a eukaryotic red alga Leitsch, Kowallik, and Douglas 1999). To see if traces of this complex symbiotic history might be preserved in the compartmentation of their energy metabolism, we investigated the compartment-specific isoforms of GAPDH and TPI in diatoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chlorarachniophytes and cryptomonads, which contain periplastid ERs (Corliss 1994) but do not belong to the stramenopiles in rRNA trees (Cavalier-Smith 1993; Van de Peer and De Wachter 1997), the periplastid space harbors remnants of an engulfed cell's nucleus, the nucleomorph (Gilson, Maier, and McFadden 1997), indicating that these algae originated via eukaryote-eukaryote endosymbioses between a phagotrophic host cell and an unicellular microalga (Gibbs 1981;Sitte 1993;McFadden and Gilson 1995;Douglas 1998). Although diatoms, like most photosynthetic heterokontflagellated protists, have not preserved a nucleomorph, molecular data indicate that their four membrane-bounded plastids descend from a eukaryotic red alga Leitsch, Kowallik, and Douglas 1999). To see if traces of this complex symbiotic history might be preserved in the compartmentation of their energy metabolism, we investigated the compartment-specific isoforms of GAPDH and TPI in diatoms.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of individual genes to accurately reflect deep phylogenetic relationships among eukaryotes is a debated issue (Embley and Hirt 1998;Philippe and Laurent 1998). TPI-GAPDH and similar gene clusters (Leitsch, Kowallik, and Douglas 1999) can help to untangle the conundrum of protist evolution.…”
Section: Diatom Mitochondria: a Missing Metabolic Link Of Organelle Ementioning
confidence: 99%
“…Köhler et al (1997) concluded that there was no a priori reason to believe that it was related to the plastids of dinoflagellates and indicated that the plastid may be derived from the green lineage. A different view has been presented on the basis of gene content and arrangement in the plastid genome, which are more consistent with a nongreen origin of the apicomplexan plastid (McFadden and Waller 1997;Blanchard and Hicks 1998;Leitsch et al 1999). These analyses are complicated by the difficulty of determining homology in the highly divergent Plasmodium falciparum plastid, but they are at least as compelling as single-gene analyses.…”
Section: Plastids In the Alveolata: A Microcosm Of Plastid Evolutionmentioning
confidence: 99%
“…Phylogenetic analyses of nucleus‐encoded genes for ribosomal RNA [11], tubulins [12], glycolytic glyceraldehyde dehydrogenase [13], the ER‐specific protein calreticulin [14] and mitochondrial Hsp60 [15], as well as the mitochondrion‐encoded coxI gene [15,16] strongly support this relationship. The endosymbiont that has developed into today's euglenid chloroplast was shown in cytological studies [1] and the comparative analysis of chloroplast genomes [17–20] to be derived from a eukaryotic green alga.…”
mentioning
confidence: 99%